Evaluating the Impact of Ethnomathematics on Mathematics Achievement: A Meta-Analysis of Studies from 2014-2024 - Putri, Linda Indiyarti; Begimbetova, Guldana; Sa’idah, Nusrotus; Murfi, Ali (MyResearch ID Publishing, 2024)
Purpose – This study aims to address the persistent challenge of low mathematics comprehension among students, often attributed to culturally irrelevant and formal approaches in teaching. Despite the potential of ethnomathematics as a culturally contextualized pedagogical approach, comprehensive evaluations of its effectiveness remain limited. This research seeks to fill this gap by conducting a meta-analysis to measure the effect size of ethnomathematics in improving mathematics education over the past decade. Methods/Design/Approach – A meta-analysis was conducted using data from 11 selected studies published between 2014 and 2024, which employed ethnomathematics in educational settings. The studies were screened based on rigorous inclusion criteria, focusing on experimental designs with control groups and sufficient statistical data for effect size calculation. Statistical analyses, including heterogeneity tests and publication bias assessments, were performed using JASP software. Findings – The meta-analysis revealed that ethnomathematics significantly enhances students' mathematics achievement, with effect sizes ranging from 0.561 to 2.698. The average effect size of 1.22 indicates a strong positive impact, demonstrating that ethnomathematics is a highly effective approach in various educational contexts, including Indonesia and Zimbabwe. The analysis also identified some heterogeneity across studies, suggesting that the effectiveness of ethnomathematics may be influenced by factors such as intervention design and population characteristics. Originality/Value – This study provides empirical evidence supporting the effectiveness of ethnomathematics as a pedagogical approach that bridges cultural contexts and mathematical concepts, enriching the curriculum and enhancing students' understanding. It contributes to the growing body of literature by validating ethnomathematics as a viable strategy for improving mathematics education, particularly in culturally diverse settings. Practical Implications – The findings suggest that educators should consider integrating ethnomathematics into their teaching practices to make mathematics more relevant and engaging for students. The study also underscores the need for curriculum developers to incorporate cultural contexts into mathematics education, fostering inclusivity and relevance. Keywords Ethnomathematics, mathematics education, meta-analysis, cultural context, educational effectiveness Paper type Research paper